Livestock grazing alters multiple ecosystem properties and services in salt marshes: a meta‐analysis. Issue 5 (23rd March 2017) - Davidson, Kate E.; Fowler, Mike S.; Skov, Martin W.; Doerr, Stefan H.; Beaumont, Nicola; Griffin, John N.
Summary: The far‐reaching impacts of livestock grazing in terrestrial grasslands are widely appreciated, but how livestock affect the structure and functions of sensitive coastal ecosystems has hitherto lacked synthesis. Grazing‐induced changes in salt marshes have the potential to alter the provision of valuable ecosystem services, such as coastal protection, blue carbon and biodiversity conservation. To investigate how livestock alter soil, vegetation and faunal properties in salt marshes, we conducted a global meta‐analysis of ungulate grazer impacts on commonly measured ecosystem properties (498 individual responses from 89 studies). We also tested stocking density, grazing duration, grazer identity, continent and vegetation type as potential modifiers of the grazing effect. The majority of studies were conducted in Europe (75) or the Americas (12), and investigated cattle (43) or sheep (22) grazing. All measures of above‐ground plant material (height, cover, above‐ground biomass, litter) were decreased by grazing, potentially impairing coastal protection through diminished wave attenuation. Soil carbon was reduced by grazing in American, but not European marshes, indicating a trade‐off with climate regulation that varies geographically. Additionally, grazing increased soil bulk density, salinity and daytime temperature, and reduced redox potential. Biodiversity responses depended on focal group, with positive effects of grazing on vegetation species richness, but negative effects on invertebrate richness. Grazing reduced the abundance of herbivorous invertebrates, which may affect fish and crustaceans that feed in the marsh. Overall vertebrate abundance was not affected, but there was provisional evidence for increases over a longer duration of grazing, potentially increasing birdwatching and wildfowling opportunities. Synthesis and applications . Our results reveal that the use of salt marshes for livestock production affects multiple ecosystem properties, creating trade‐offs and synergies with other ecosystem services. Grazing leads to reductions in blue carbon in the Americas but not in Europe. Grazing may compromise coastal protection and the provision of a nursery habitat for fish while creating provisioning and cultural benefits through increased wildfowl abundance. These findings can inform salt marsh grazing management, based on local context and desired ecosystem services. Abstract : Our results reveal that the use of salt marshes for livestock production affects multiple ecosystem properties, creating trade‐offs and synergies with other ecosystem services. Grazing leads to reductions in blue carbon in the Americas but not in Europe. Grazing may compromise coastal protection and the provision of a nursery habitat for fish while creating provisioning and cultural benefits through increased wildfowl abundance. These findings can inform salt marsh grazing management, based on local context and desired ecosystem services.